2020
DOI: 10.2215/cjn.11440919
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disorders of the Glomerular Filtration Barrier

Abstract: The glomerular filtration barrier is a highly specialized capillary wall comprising fenestrated endothelial cells, podocytes, and an intervening basement membrane. In glomerular disease, this barrier loses functional integrity, allowing the passage of macromolecules and cells, and there are associated changes in both cell morphology and the extracellular matrix. Over the past three decades there has been a transformation in our understanding about glomerular disease, fueled by genetic discovery, and this is le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 59 publications
0
24
0
1
Order By: Relevance
“…Nephrotic syndrome can be caused by dysfunctions of podocytes, endothelial cells, or GBM, indicating that all 3 components are essential for maintaining the glomerular filtration barrier. Extensive genetic studies of nephrotic syndrome have identified mutations in genes important for establishing and maintaining the barrier (1).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotic syndrome can be caused by dysfunctions of podocytes, endothelial cells, or GBM, indicating that all 3 components are essential for maintaining the glomerular filtration barrier. Extensive genetic studies of nephrotic syndrome have identified mutations in genes important for establishing and maintaining the barrier (1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that immune-mediated glomerular injury involves activation of both innate and adaptive immunity, which leads to the clinical and pathological manifestation of the disease. Over the past 10 years, more than 80 genes causing glomerular barrier dysfunction have been identified [2]. With the emergence of human genetic studies, understanding which gene sequence is the main trigger for the immune system malfunction became a very powerful tool to uncover the molecular drivers of these diseases and help find potential targeted therapy.…”
Section: Integrating Genomics Transcriptomics and Proteomicsmentioning
confidence: 99%
“…Varied clinical manifestation may be due to the polymorphic gene expression in the immune system as well as at the glomerular filtration barrier site, which comprises podocytes, endothelial cells, and intervening glomerular basement membrane [2]. In addition to the multiple immune cascade pathways, underlying complex molecular and cellular processes are identified by proteomics and transcriptomics in glomerular disorders like Minimal Change Disease and focal segmental glomerulosclerosis (FSGS) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Additional proteins that maintain slit diaphragm proteins, such as CD2AP, play vital roles in GFB maintenance. Podocytes are essential in GFB function, underscored by the discovery of pathogenic mutations to proteins involved in maintaining podocyte structure that are causal to proteinuric forms of kidney disease ( Vivante and Hildebrandt, 2016 ; Li et al, 2020a ). The GBM is formed by secreted products from both podocytes and endothelial cells during glomerulogenesis ( St John and Abrahamson, 2001 ).…”
Section: The Functional Barriermentioning
confidence: 99%